International construction of area studies in France during the Cold War: Insights from the École Pratique des Hautes Études 6th Section. (October 2016) - Popa, Ioana
An Area Studies Division was created at the 6 th Section of the École Pratique des Hautes Études (Paris) in the mid-1950s. It was devoted to several world regions, including the USSR and eastern Europe. This article investigates the links between its institutionalization and the international scientific and financial transfers underpinning it: the transatlantic support granted to the nascent division by the Rockefeller and Ford foundations and the academic cooperation programme that it launched with eastern Europe. The Russian, Soviet and East European programme served, thus, as an East/West interface and a platform for broader intellectual exchanges. Local French scientific, academic and political rationales favoured the specific pathways it took. The article also shows that the EPHE 6 th Section was discreetly linked with American players in Cold War intellectual warfare whose forms of action gradually changed in the context of the thaw. In particular, it had connections with the Congress for Cultural Freedom. These collusions attest to the entanglement of scientific and political issues, their intricacies increasing when external factors compounded domestic ones.